ANTIMICROBIAL SUSCEPTIBILITY, MICROBIAL PROFILE AND PREVALENCE OF MDR/XDR PATHOGENS CAUSING MEDICAL DEVICE-ASSOCIATED INFECTIONS: A SINGLE CENTRE STUDY. - Raj, Kunal; Kumar, Jag Mohan; Tudu, Lalchand; Bhattacharya, Pradip Kumar; Kumar, Amit (Student's Journal of Health Research Africa, 2024)
Background The development of nosocomial infection associated with pathogens that are multi-drug resistant and extensively drug-resistant leads to serious complications in hospitalized patients. Since this type of infection has limited treatment options it is necessary to identify and determine their prevalence. This study is conducted to determine the Microbial Profile, Antimicrobial Susceptibility, and Prevalence of MDR/XDR Pathogens Causing Medical Device Associated Infections at our institute. Materials and Methods The patients admitted at the RIMS Ranchi were included in the study. The demography and other clinical characteristics of the patients were recorded. The CLABSI, CAUTI, and VAP were confirmed in the patients. The causative pathogen was isolated. The microbiology profile, resistance, and susceptibility pattern of these organisms were studied. Results Among the 110 patients, 65 were confirmed to have MDAIs based on positive culture results. The average age of the patients was 43.5 ± 5 years, with a majority being male. Comorbidities included liver disorders (30.7%), cardiovascular disorders (29.2%), and renal disorders (21.3%). Immunosuppression was seen in 80% of patients. The infections identified were central line-associated bloodstream infections (53.8%), catheter-associated urinary tract infections (23.07%), and ventilator-associated pneumonia (23.07%). Of the 80 pathogens isolated, 54 were MDR, and 20 were XDR. Carbapenem resistance was noted in 35% of the isolates. Fungal resistance to amphotericin B and fluconazole was observed in 8.75% of cases. Two patients with ventilator-associated pneumonia did not survive. Conclusion MDAIs are inevitable, among them central-line bloodstream infection is found in most patients. The occurrence of resistance among the patients severely reduces the treatment options available and increases the complexities of the treatment. Recommendation Preventative measures and analysis of microbiology profiles are necessary to reduce the occurrence of infection associated with medical devices.